Metodologia multicritério para seleção de fornecedores de embalagens em agroindústrias - Fragoso, Barbara (2024)
Choosing suppliers is a crucial decision for any company, as it can directly impact the quality of products or services, as well as risk reduction, production costs, delivery times, and customer satisfaction. However, determining suppliers is not always straightforward, with numerous variables complicating the decision-making process. Therefore, it is essential to dedicate time and resources to evaluate available options and choose the most suitable suppliers for any company. This concern arose because, although the company operated with an established list of suppliers based on predefined criteria, the lack of depth led to questions about maintaining these relationships or adopting in-house production of raw materials, seeking alternatives to become independent of suppliers. However, there are various tools that can assist in supplier selection, including market research, performance evaluation, auditing, certifications, supplier visits, cost-benefit analysis, and multicriteria analysis techniques, which will be addressed in this study. Using multicriteria analysis can help evaluate each supplier more comprehensively and balancedly in relation to these criteria, allowing a well-founded and coherent choice with the company's needs and objectives. In this regard, this work began with the application of Methodi Ordinatio, which allowed classifying articles according to their scientific relevance. This was followed by a case study in an agribusiness with the assistance of a multidisciplinary team to analyze/evaluate and make decisions in the selection of packaging suppliers. With the team established, 17 evaluation criteria and 6 alternatives for judgment were selected. Subsequently, the AHP method was proposed, which demonstrated efficiency in prioritizing criteria, evaluating alternatives, and consistency in assessment. Next, the ELECTRE I method was applied, which helped identify dominant alternatives, dealt with uncertainties and subjective preferences of decision-makers, identified preference relations, allowing for structured decision-making. Finally, the application of methods in the research highlighted suppliers F2 and F6 as potential candidates, demonstrating the effectiveness of the methodological approaches employed and the satisfaction of decision-makers.